PENGALAMAN KELUARGA DALAM PENANGANAN SERANGAN PERTAMA PADA PASIEN STROKE - Deci Ratnawardani; Wasisto Utomo; Safri Safri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Stroke is a health problem that associated with blood circulation disorder in the brain. The problem of stroke is very complex, especially first aid for stroke patient. The purpose of this research is to explore family experience to give first aid in stroke patient. The design of this research is qualitative methode with phenomenology approach. The partisipant is 4 people that the family have experience in stroke first aid and it choosed by using purpose sampling. This research have 4 theme: 1) family knowledge about stroke, there are the definition, sign and symptom, and risk factor, 2) stroke first aid, 3) time to find help, 4) using health facility. The result of this research hoped can be the reference for the family about first aid for stroke or as a supporting data for the next researcher that want to research about stroke. Keyword: family experience, phenomenology study, stroke